Pengembangan Berpikir Kreatif pada Pembelajaran PAI dalam Menghadapi Tantangan Pendidikan Islam Menuju Society 5.0 - Itsnan Mahfuddin Al Mubarok; Puji Rahayu; Intan Pratiwi; Zulfikri Alwy Jauhari; Anis Khusnul Inayah (IJoIS: Indonesian Journal of Islamic Studies, 2023)
The research objective of this article is to explain the importance of developing creative thinking and its implementation in learning Islamic Religious Education (PAI) and its relation to Islamic education in the Society 5.0 era. The concept of creative thinking used is Bloom's Taxonomy learning theory. The research approach uses library research with content analysis methods. Sources of data come from journals and books in the field of Islamic education and the development of creative thinking using the bloom taxonomy concept. Data collection is carried out by collecting related references, both manually and digitally. After the data is collected, it is then displayed, reduced and constructed so that a whole and contemporary new concept emerges. This is increasingly urgent because the challenges of education in the era of society 5.0 require that the world of education be able to produce graduates who are responsive to technology.